Studi Pendahuluan Pengembangan Bahan Ajar Tema Berufe untuk Siswa Kelas X Menggunakan Model ADDIE - Tania Try Habsari Tampubolon; Anjeli Zega; Meily Zahra; Moses Sitinjak (LOKAKARYA, 2026)
This study aims to investigate the initial needs and develop German teaching materials on the theme Berufe (professions) for 10th-grade students. The research employs a qualitative descriptive approach through classroom observation, interviews with teachers and students, and analysis of existing teaching materials. The preliminary study indicates that the current materials are conventional, lack contextual relevance, and offer limited interactive media, resulting in a teacher-centered learning process. Teachers expressed the need for teaching materials that support communication skills and integrate both local and German culture, while students preferred content featuring simple dialogues, real-life situations, and visual media. Based on these findings, the teaching materials were developed using the ADDIE model, covering analysis, instructional design, module development, classroom implementation, and evaluation for improvement. The developed materials are interactive, contextual, and practical, expected to enhance students’ learning motivation, communicative competence, and meaningful learning experiences. This study provides a foundation for creating German teaching materials that are relevant, adaptive, and aligned with students’ needs.